Functionalization of Fe3O4/SiO2 with N-(2-Aminoethyl)-3-aminopropyl for Sorption of [AuCl4]- - Nuryono Nuryono; Mighfar Syukur; Agus Kuncaka; Satya Candra Wibawa Sakti (Indonesian Journal of Chemistry, 2016)
Synthesis of Fe3O4/SiO2 modified with N-(2-aminoethyl)-3-aminopropyl group (Fe3O4/SiO2/ED) via coating method and its application for adsorption-desorption of anionic gold in aqueous solution have been conducted. The synthesized product was characterized with an X-ray diffractometer (XRD), a Fourier transform infrared (FT-IR) spectrophotometer and a transmission electron microscopy (TEM). Adsorption of Au(III) was conducted in a batch system and the variables included pH, contact time, and initial concentration were investigated. Results showed that magnetite/silica has been successfully functionalized with N-(2-aminoethyl)-3-aminopropyl in a homogeneous system. Kinetics study showed that adsorption of Au(III) followed the pseudo-second order model with rate constant of 0.710 g mmol L-1min-1. Furthermore, the experimental data fitted well with the Langmuir isotherm model with the maximum adsorption capacity for Au(III) of 142.9 mg g-1 and the energy of 25.0 kJ mol-1. Gold loaded on the Fe3O4/SiO2/ED could be easily desorbed with 0.2 mol L-1 HCl containing 2 wt.% of thiourea with recovery of 99.8%. Fe3O4/SiO2/ED was reusable and stable in 5 cycles of adsorption-desorption with recovery more than 90%. Fe3O4/SiO2/ED showed high selectivity towards Au(III) in the multimetal system Au(III)/Cu(II)/Cr(VI) with the coefficient selectivity for αAu-Cu of 227.5and for αAu-Cr of 12.3.